1990
DOI: 10.1093/schbul/16.2.229
|View full text |Cite
|
Sign up to set email alerts
|

Are Gender Differences in Schizophrenia Reflected in Brain Event-related Potentials?

Abstract: Numerous studies have reported relationships between gender and cerebral event-related potentials (ERPs) recorded from the human scalp. Recent studies have suggested that the influences of gender on ERPs may differ in persons with schizophrenia compared to healthy controls. In a further evaluation of the influences of this critical subject variable on ERP characteristics in schizophrenia, ERPs of age- and gender-matched groups (n = 72 each) of unmedicated schizophrenic patients and healthy controls were compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

1992
1992
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 59 publications
0
16
0
Order By: Relevance
“…Some have reported that schizophrenic males have different morphological and physiological brain abnormalities, in addition to a lower family risk, than schizophrenic females. 9–20 Seeman and Lang hypothesized that estrogens account for many of the observed gender differences. 21 They noted that estrogens increase the density of dopamine type 2 receptors as do neuroleptics, and high levels of estrogens may serve a protective function in the onset of schizophrenia.…”
Section: Discussionmentioning
confidence: 99%
“…Some have reported that schizophrenic males have different morphological and physiological brain abnormalities, in addition to a lower family risk, than schizophrenic females. 9–20 Seeman and Lang hypothesized that estrogens account for many of the observed gender differences. 21 They noted that estrogens increase the density of dopamine type 2 receptors as do neuroleptics, and high levels of estrogens may serve a protective function in the onset of schizophrenia.…”
Section: Discussionmentioning
confidence: 99%
“…The present data indicate that the influence of gender, in addition to chronological age (Freedman et al 1987a;Papanicolaou et al 1984), must be considered in studies of auditory gating. However, the relevance of the observed gender differences to psychopathology is unclear because of reports that psychiatric illness appears to modify normal gender influences on cortical evoked potentials (Josiassen et al 1990;Shagass et al 1972).…”
Section: Discussionmentioning
confidence: 99%
“…Roemer and Shagass 21 claimed medication reduced visual but not overall auditory N1 amplitudes. Josiassen et al 22 tested 72 unmedicated schizophrenia subjects and 72 controls and reported smaller N1 to clicks in schizophrenia. Kessler and Steinberg 9 reported reduced N1 in unmedicated paranoid schizophrenia but not in unmedicated residual/undifferentiated schizophrenia.…”
Section: Introductionmentioning
confidence: 99%